Information Flow Analysis in Kogonada's 'Columbus' - Maloletkin, Maksim Fedorovich (Философия и культура, 2025)
The article investigates the specifics of transmitting authorial intent from filmmaker to viewer in contemplative cinema, utilizing Kogonada's 'Columbus' (2017) as the primary analytical material. The subject of comprehensive systemic analysis encompasses informational transformations arising throughout the communicative transmission process in "slow" cinema. The study examines in detail the distinctive characteristics of informational aberrations within the context of intentional reduction of dramatic stimuli, analyzing key scenes featuring understatement, communicative breakdowns, and architectural framing of characters. Particular attention is devoted to the role of modernist buildings as active participants in the communicative process, the influence of intermediary mechanisms (festival distribution, criticism, digital platforms) on final audience reception, and cognitive aspects of viewer decoding of contemplative content within contemporary fragmented media consumption patterns dominated by clip-based thinking. The research employs an interdisciplinary approach, integrating Shannon-Weaver information theory, Hall's encoding-decoding paradigm, and Miller's cognitive limitation framework. The methodology encompasses detailed frame-by-frame analysis of pivotal episodes (the "guide mode" dialogue, telephone conversation, failed party) with temporal markers and semiotic analysis of architectural elements as visual codes. A systematic examination of contemplative cinema through the lens of informational flow from filmmaker to audience via intermediary channels reveals specific mechanisms of informational transformation within minimalist aesthetic frameworks. The investigation establishes that in slow cinema, informational noise emerges not through redundancy but via deliberate understatement, which functions as a productive artistic device for meaning generation. The study identifies the role of architectural elements in shaping communicative processes and influencing viewer perception, examines the specificity of intermediary filtering mechanisms within independent film production systems and their selective audience impact, and proposes a reconceptualization of traditional approaches to analyzing viewer reception regarding contemplative formats. The research findings contribute to film theory frameworks for studying and analyzing audiovisual materials. This work continues a series of scholarly articles devoted to the problematic of informational noise in screen arts, commenced by the author in 2023.